Main Problems of Diabetes Mellitus Type 2 Patients in Keeping Diet - Volkova, Antoņina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
A research has been carried out to assess the awareness of patients about the importance of diet, the availability of information and to make the diabetes patients with mellitus type 2 realize the urgency of dieting. The first part looks into theoretical sources and statistics about how widespread diabetes mellitus type 2 is and the importance of a healthy diet. The practical part of the research consists of the survey results. The method of quantitative research was applied. The conclusions and suggestions have been made based on the research results.